Stent strut breakage using high‐pressure balloons for bifurcation stenting and subsequent percutaneous pulmonary valve replacement using the Edwards Sapien THV - Violini, Roberto; Vairo, Ugo; Hijazi, Ziyad M. (Catheterization and cardiovascular interventions, 2013)
This report describes the use of the Edwards Sapien THV in a patient who had a short regurgitant/stenotic homograft with early bifurcation stenoses of the pulmonary arteries. A 48‐mm AndraStent was positioned in the right pulmonary artery‐homograft jailing the left pulmonary artery (LPA). To have an unobstructed access to the LPA, the stent strut leading to the LPA was broken using high‐pressure balloon. A 23‐mm Edwards Sapien THV was positioned in the stented homograft just proximal to the LPA origin with resolution of the stenosis and regurgitation. © 2012 Wiley Periodicals, Inc.